Significance of the Institute of Release from Criminal Responsibility for the Lithuanian Criminal Policy - Švedas, Gintaras (Teisė, 2024)
Goals of criminal liability can be achieved without imposing a punishment or the actual execution of the punishment imposed on a person who has committed a criminal act. Therefore, modern Lithuanian Criminal Law provides for the following three forms of criminal liability realization: 1) imposition of punishment, 2) release from criminal liability, and 3) suspension of the execution of punishment or release from the execution of punishment. The traditional form of implementing criminal liability recognizes the imposition of punishment (sentencing). In this case, the court that has found a person guilty of a criminal act has the duty and the right to impose a punishment on him/her. Statistical data confirm that sentencing is essentially the main form of realization of criminal liability in Lithuania, which is applied in an average of two-thirds (or about 66 percent) of decisions in criminal cases. Meanwhile, release from criminal liability or suspension of execution of punishment and release from the execution of punishment can be considered as additional forms of realization of criminal liability. Statistical data show that the institute of release from criminal liability remained stable in the second place and consistently accounted for a fraction more than one quarter (or about 27 percent) of decisions on criminal cases each year. Meanwhile, the statistical data of the application of the institute of suspension of execution of punishment and release from the execution of punishment show that this form of realization of criminal liability solves only a relatively small (or about 7 percent) share of criminal cases.Release from criminal liability as a form of realization of criminal liability in Lithuania can be with or without the application of penal or reformative measures. Chapter VI of the General Part of the Criminal Code of Lithuania “Release from Criminal Liability” essentially provides the 8 main, general types of release from criminal liability: release from criminal liability when a person or criminal act loses its dangerousness (Article 36 of the CC), release from criminal liability due to minor relevance of a crime (Article 37 of the CC), release from criminal liability upon reconciliation between the offender and the victim (Article 38 of the CC), release from criminal liability on the basis of mitigating circumstances (Article 39 of the CC), release from criminal liability when a person actively assisted in detecting the criminal acts committed by members of an organized group or a criminal association (Article 39(1) of the CC), release of a whistleblower from criminal liability (Article 39(2) of the CC), release from criminal liability on bail (Article 40 of the CC), and Chapter X of the General Part of the Criminal Code of Lithuania “Peculiarities of Criminal Liability of Juveniles” – release of a minor from criminal liability (Article 93 of the CC). The greatest influence on the Lithuanian criminal system in the last six years (2018–2023) has been exerted by such types of release from criminal liability as release from criminal liability upon reconciliation between the offender and the victim and release from criminal liability on bail, and, to a lesser extent – release from criminal liability due to the minor relevance of a crime. Meanwhile, other types of release from criminal liability for objective reasons, consisting of the regulation of the entire application grounds and individual requirements, practically do not affect the criminal policy. On the other hand, some of these types of release from criminal liability (such as release from criminal liability due to the minor relevance of a crime, release from criminal liability upon reconciliation between the offender and the victim, release from criminal liability on the basis of mitigating circumstances and release from criminal liability on bail) have the potential to exert greater influence on the criminal policy, and therefore support the amendments and additions to the Criminal Code which aim to abandon unreasonable restrictions and expand the legal prerequisites for the application of individual types of release from criminal liability.
Keywords: criminal liability; criminal policy; release from criminal liability